Sexual function in patients with schizophrenia on anti-psychotics: a comparative study of hyperprolactinemia-inducing and hyperprolactinemia non-inducing antipsychotics - Natarajan Shanmugasundaram; Jayasutha Jayram; Sobana R.; Mayakrishnan S.; Harini S.; Senthil Kumar E.; Charupriya Mani; Lisiya Soundarajan; Lourdu Akshaya; Sindhu Selvam (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Sexual dysfunction is a common but often under-recognized adverse effect in patients with schizophrenia receiving antipsychotic therapy. Hyperprolactinemia induced by certain antipsychotics has been implicated as a major contributing factor. This study aimed to compare sexual function among patients receiving hyperprolactinemia-inducing and hyperprolactinemia non-inducing antipsychotics and to assess whether sexual dysfunction is related to antipsychotic-induced hyperprolactinemia or the underlying illness itself. Methods: A prospective observational study was conducted in the Department of Psychiatry at Sri Ramachandra Hospital, Chennai, from March to July 2025. Sixty patients diagnosed with schizophrenia according to ICD-10 criteria and receiving antipsychotic therapy were enrolled. Patients were categorized into two groups: hyperprolactinemia-inducing antipsychotics (olanzapine, haloperidol, risperidone) and hyperprolactinemia non-inducing antipsychotics (aripiprazole, cariprazine, lurasidone). Sexual function was assessed using the Arizona Sexual Experience Scale (ASEX), and serum prolactin levels were measured. Statistical analyses included independent t-tests and one-way ANOVA, with p